Solution of mixed problem for a poroelasticity system described by homogeneous equations with three elasticity parameter: Solution of mixed problem for a poroelasticity system described by homogeneous equations with three elasticity parameter - Rakhimov , Abror (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
The mixed problem is considered for a one-dimensional system of equations describing the propagation of longitudinal waves in porous media saturated with liquid in a reversible hydrodynamic approximation. A formula for solving this problem is obtained.